Needs Analysis of Interactive Multimedia Based on Drill and Practice to Improve Motivation and Critical Reading Skills in Elementary Schools - Abdulah Abdulah; Muhammad Nur Wangid (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this study was to analyze the needs of interactive multimedia based on drill and practice in elementary school. This research was conducted at an elementary school located in Sleman Regency, Yogyakarta, Indonesia. Participants in this study were 93 fifth grade students at elementary schools. The data in this study were obtained using a needs questionnaire from interactive multimedia based on drill and practice. The results of this study indicate that critical reading skills and student motivation are still low. So that in learning activities appropriate learning media is needed. Based on the results of the analysis of the needs for instructional media, students stated that they needed interactive multimedia based on drill and practice. The results of this study indicate that it is necessary to develop interactive multimedia based on drill and practice.Abstrak: Tujuan penelitian ini adalah menganalisis kebutuhan multimedia interaktif berbasis drill and practice di sekolah dasar. Penelitian ini dilakukan di sebuah sekolah dasar yang terletak di Kabupaten Sleman, Yogyakarta, Indonesia. Partisipan dalam penelitian ini adalah 93 siswa kelas V di sekolah dasar. Data dalam penelitian ini diperoleh dengan menggunakan angket kebutuhan dari multimedia interaktif berbasis drill and practice. Hasil penelitian ini menunjukkan bahwa kemampuan membaca kritis dan motivasi belajar siswa masih rendah. Sehingga dalam kegiatan pembelajaran diperlukan media pembelajaran yang sesuai. Berdasarkan hasil analisis kebutuhan media pembelajaran, siswa menyatakan membutuhkan multimedia interaktif berbasis drill and practice. Hasil penelitian ini menunjukkan bahwa perlu dikembangkan multimedia interaktif berbasis drill and practice.